Determination of nucleobase-pairing free energies from rotamer equilibria of 2-(methylamino)pyrimidines. Issue 74 (28th August 2019) - Štoček, Jakub Radek; Bártová, Kateřina; Čechová, Lucie; Šála, Michal; Socha, Ondřej; Janeba, Zlatko; Dračínský, Martin
Abstract : A straightforward method is proposed for the determination of free energies of nucleobase pairing by monitoring conformational changes upon intermolecular binding. Abstract : A fast straightforward method for the determination of free energies of modified nucleobase pairing is proposed. The method is based on the nuclear magnetic resonance (NMR) spectroscopy monitoring of conformational changes of 2-(methylamino)-pyrimidines upon intermolecular binding.